PERANCANGAN KARAKTER TOKOH VISUAL NOVEL DARK NIGHT - SEPTIA FAKHIRA RISTI, Drs. Syafwan, M.Si., Dini Faisal, S.Ds., M.Ds. (DEKAVE : Jurnal Desain Komunikasi Visual, 2019)
The purpose of this design is to produce characters in the visual novel Dark Night that matches the character’s background based on Indonesian culture, Dayak, Bali and Batak.The design characters of visual novel Dark Night using black box & glass box design methods and conducting research and collecting reference data about Dayak, Balinese and Batak culture through books, printed media, journals, internet, thesis and other works relevant.The results of this design use the main media in the form of Artbook because this media can display all the characters that have been designed in detail as well as the background of each character's story and supporting media : audio visual, t-shirt, poster, x-banner, cover DVDs, DVD labels, keychains and stickers.Keyword : Characters, Visual novel